Anesthetic management in a patient with Arnold‐Chiari malformation type 1, 5: A case report. Issue 2 (4th February 2022) - Coviello, Antonio; Golino, Ludovica; Posillipo, Concetta; Marra, Annachiara; Tognù, Andrea; Servillo, Giuseppe
Abstract: A 42‐year‐old male patient with Arnold‐Chiari malformation type 1, 5 (ACM‐1, 5) came to implant a hip prosthesis. He underwent a previous general anesthesia, with difficult airway management and complication in awakening. In this second surgery, an extradural approach was preferred to keep intracranial pressure and hemodynamics stable. Abstract : Scientific literature is not very rich in information regarding the best anesthesiological approach to patients with Arnold‐Chiari malformation type II (ACM‐II). We therefore wanted to provide our experience with an ACM‐II patient.